2022
DOI: 10.1039/d1cc06731a
|View full text |Cite
|
Sign up to set email alerts
|

Modulating intramolecular electron and proton transfer kinetics for promoting carbon dioxide conversion

Abstract: A novel pentagon-heptagon paired azulene group which possesses large dipole moment is immobilized to porphyrin. The as–prepared azulene iron porphyrin exhibits narrower bandgap and higher electrocatalytic CO2 reduction activity than...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…To date, diverse analogues of porphyrins (including N-confused porphyrins [15], tetraaza [14], annulenes [16], and conjugated N 4 -macrocyclic ligand [17]) have been reported to coordinate with a large number of metal ions, exhibiting unique optoelectronic properties. In another way, modification of porphyrins with functional groups has been confirmed as a good strategy for improving their CO 2 RR performance [18][19][20]. For example, we have reported that the tertiary amine group could enhance CO production due to the enrichment of CO 2 around molecules by amine groups [18].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To date, diverse analogues of porphyrins (including N-confused porphyrins [15], tetraaza [14], annulenes [16], and conjugated N 4 -macrocyclic ligand [17]) have been reported to coordinate with a large number of metal ions, exhibiting unique optoelectronic properties. In another way, modification of porphyrins with functional groups has been confirmed as a good strategy for improving their CO 2 RR performance [18][19][20]. For example, we have reported that the tertiary amine group could enhance CO production due to the enrichment of CO 2 around molecules by amine groups [18].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, some π-conjugated groups (like azulene, pyrene, etc.) were grafted onto the metal tetraphenylporphyrins to extend their conjugated system with lower bandgaps, resulting in the high electrocatalytic CO 2 conversion [19,20]. Unfortunately, synthesis of these molecules often suffers from tedious synthetic steps with low reaction yields.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion of fossil fuels has led to serious environmental and climate challenges. An effective strategy to mitigate carbon emissions and harness carbon dioxide as a resource involves the conversion of CO 2 into fuels and valuable chemicals using renewable electricity. , In the CO 2 RR systems, the high stability of catalysts is crucial. Many electro-catalysts, typically in powder form, are applied to conductive substrates via polymer binders such as Nafion.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical conversion of carbon dioxide (CO 2 ) into value-added products, such as carbon monoxide (CO), formic acid, ethylene, and ethanol, by utilizing renewable energy sources is an appealing approach to achieving carbon neutrality and energy storage. 1,2 Various inexpensive and abundant transition metal-based electrocatalysts, such as those based on Fe, [3][4][5][6] Co, [7][8][9][10] Ni, [11][12][13][14][15][16] Cu, [17][18][19] and Bi (ref. [20][21][22], have been widely used to catalyze the CO 2 reduction reaction (CO 2 RR).…”
Section: Introductionmentioning
confidence: 99%